E-COMMERCE: ROLE, CONCEPT, DEVELOPMENT DIRECTIONS - Odijon Sattarov; Khatamov Nurbek (International Journal of Innovations in Engineering Research and Technology, 2022)
The history of e-commerce dates back to the 60s of the twentieth century and is characterized by the introduction airline booking systems. Further, its development is facilitated by the creation of inventory management systems, the emergence of computer networks and data transmission systems, payment cards and other electronic payment systems, and as well as the commercialization of the Internet.